Molecular characterization of local isolates of infectious bursal disease virus from broiler chickens in Iraq - Mohammed, M.H.; Ali, G.H.; Hasan, I.I. (Penerbit Universiti Kebangsaan Malaysia, 2014)
The present study was conducted to characterize a new field isolates of infectious bursal disease virus (IBDV) by reverse transcription-polymerase chain reaction (RT-PCR) and partial sequencing of VP2 gene. The virus could be detected in five of seven field samples from broiler chickens in Iraq. Nucleotide sequences of field isolates were compared with 33 reported IBDV strains from different parts of the world. Nucleotide substitutions at I242, Q249, Q252, I256, D279, A284, I294, S326 and S330 specific for very virulent (vv) strains, were maintained in all the field isolates. Deduced amino acid substitutions A222, I242, Q249, Q252, I256, D279, A284, I294, S326 and S330 specific for vvIBDV strains were also present in all the isolates. Phylogenetic analysis showed that all the field isolates in the present study were closely related to reported UK (XZh) and Japan (OKYM) field isolates. Further comprehensive investigations will provide more information on the distribution, variability, phylogenetic relationships of different vvIBDV isolate in Iraq and other parts of the worlds.